Contributions to the knowledge of North American tenebrionids of the subtribe Cylindrinotina (Coleoptera: Tenebrionidae: Helopini) - Nabozhenko, Maxim; Nikitsky, Nikolay; Aalbu, Rolf (Zootaxa, 2016)
Three North American species of Helops are reassigned to the genus Nalassus: N. aereus (Germar, 1824), comb. n., N. californicus (Mannerheim, 1843), comb. n., N. convexulus (LeConte, 1861), comb. n. Current distributions as well as paleo distributions are discussed. A lectotype is designated for Helops californicus.